Assessment of reconfiguration schemes for Reconfigurable Manufacturing Systems based on resources and lead time. (February 2017) - Puik, Erik; Telgen, Daniel; van Moergestel, Leo; Ceglarek, Darek
Abstract: Reconfigurable manufacturing equipment is developed to meet the growing demand for more agile production. Agile manufacturing technology can improve the turnover of a company if it enables fast market introduction for volume production. Modular reconfiguration, defined as changing the structure of the machine, enables larger variation of products on a single manufacturing system; these solutions are called Reconfigurable Manufacturing Systems (RMS). The quality of RMS, and the required resources to bring it to reliable production, is largely determined by a swift execution of the reconfiguration process. This paper proposes a method to compare alternatives for the ways to implement reconfiguration. Three classes of reconfiguration are defined to distinguish the impact of the proposed alternatives. The procedure uses a recently introduced index method for development of RMS process modules, based on the Axiomatic Design methodology. Weighting factors are used to calculate the resources and lead time needed to implement the reconfiguration process. Application of the method leads to quick comparison of alternatives in the early stage of development. Successful execution of the method was demonstrated for the manufacturing process of a 3D measuring probe. Highlights: Reconfigurable Manufacturing Systems (RMS) are an answer to quickly changing needs for manufacturing of products. The paper presents a method for assessment of modular equipment setups to compare the resources and lead-time. The analysis focusses on the decomposed manufacturing system; how it is built from modular parts or 'Process Modules'. The process modules are investigated and characterised in three classes; 'repeat', 'adapt', and 'expand'. The classification is performed with an index method that is based on the axiomatic design methodology. The method does perform well. An inventory is made of strengths drawbacks for further optimisation.